NEETs in Europe: from Plural (In)visibilities to Public Policies - Vieira, Maria Manuel (2021)
In recent decades, a considerable amount of research on youth transitions (Brooks 2009; du Bois-Reymond and Chisholm 2006; Pais and Ferreira 2010) has pointed to the complexity of contemporary young people’s lives, as progression into adulthood has become increasingly prolonged, fragmented and largely unpredictable. More re cently, the high level of youth unemployment rates observed during the economic crisis became a matter of deep concern for political authorities at the global level (Bendit and Miranda 2015; Eurofound 2012; Inui 2005; Longo and Gallant 2016; Longle 2016; Henderson et al. 2017; Jacinto 2016).